Trust Based Social Commerce Price and Consumer Behavior in Jastip Indonesia - Suryari Purnama; Cicilia Sriliasta Bangun; Ramiro Santiago Ikhsan (Pandawan, 2026)
The rapid growth of social commerce in Indonesia has given rise to informal digital business models such as Jastip (Jasa Titip) personal shopping service, which represents a grassroots form of digital transformation among Micro, Small, and Medium Enterprises (SMEs). Operating entirely through digital platforms such as Instagram and WhatsApp, Jastip exemplifies how technology- driven commerce is reshaping consumer behavior and SME competitiveness beyond formal marketplace structures. This study empirically examines the influence of three key digital commerce antecedents, Online Customer Review (OCR), Shopping Experience (SE), and price on Online Purchase Intention (OPI), mediated by Consumer Trust (CT), in the Jastip context. A quantitative approach was employed using Structural Equation Modeling (SEM-LISREL) with 115 respondents from Generation Y (aged 24–39 years). Results demonstrate that price is the only antecedent with a significant direct effect on consumer trust (t-value = 2.84), which in turn strongly predicts online purchase intention (t-value = 5.76). Consumer trust fully mediates the price purchase intention relationship (complete mediation), while OCR and shopping experience were not found to significantly predict trust in this informal digital commerce context. These findings offer strategic implications for Jastip operators and digital SME policymakers, emphasizing that transparent pricing and trust architecture are the primary digital levers for driving purchase intention in informal social commerce platforms.